2012
DOI: 10.1890/es12-00034.1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic versus static occupancy: How stable are habitat associations through a breeding season?

Abstract: Most studies of habitat use by animals assume that there is little movement by individuals once they have settled. This assumption of static occupancy is especially true in studies of birds, even though many bird species are known to abandon failed nest sites in search of better habitat or to move up a habitat gradient as the season proceeds. If birds move into different habitats as the season progresses, studies assuming static use of habitat may provide misleading or incomplete inference into habitat use. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 45 publications
2
25
0
Order By: Relevance
“…Nevertheless, numerous studies have interpreted these dynamic rates as evidence of within‐season dispersal (e.g. Betts et al., ; McClure & Hill, ; Otto & Roloff, ; Rota et al., ). Indeed, Rota et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, numerous studies have interpreted these dynamic rates as evidence of within‐season dispersal (e.g. Betts et al., ; McClure & Hill, ; Otto & Roloff, ; Rota et al., ). Indeed, Rota et al.…”
Section: Discussionmentioning
confidence: 99%
“…Because multiple studies (e.g. McClure & Hill, ; Rota et al., ) compare static and dynamic occupancy models to test for evidence of dynamics, we compared model pairs with a common approach (Dail & Madsen, ; Rota et al., ; Self & Liang, ). Static occupancy models are special cases of their dynamic counterparts where dynamic parameters are constrained to be zero.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that most species of forest birds examined exhibited apparent within‐season distribution dynamics. Our results add to growing evidence that within‐season site occupancy may be less static than traditionally assumed (Betts et al ., ; McClure & Hill, ). For example, McClure & Hill () also found dynamic occupancy models outperformed static occupancy models in a south‐eastern U.S. forest bird community suggesting birds were shifting sites within a breeding season.…”
Section: Discussionmentioning
confidence: 99%
“…Our results add to growing evidence that within‐season site occupancy may be less static than traditionally assumed (Betts et al ., ; McClure & Hill, ). For example, McClure & Hill () also found dynamic occupancy models outperformed static occupancy models in a south‐eastern U.S. forest bird community suggesting birds were shifting sites within a breeding season. Radio tracking (Klemp, ; Gow & Stutchbury, ), territory mapping (Brambilla & Rubolini, ) and mark–recapture studies (Gilroy et al ., ) have also demonstrated within‐season movements and site shifts in birds.…”
Section: Discussionmentioning
confidence: 99%